(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Dinosaur footprints are described from the Lower Sandstone Unit of Kersa area, eastern Ethiopia. These are thought to belong to an early branch of theropods, and reported for the first time from Ethiopia. The evidence supports a Late Triassic age for the Lower Sandstone Unit in eastern Ethiopia and also throws light on its probable depositional environment.